2014
DOI: 10.1149/06117.0055ecst
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fluorescence Correlation Spectroscopy in the Characterization of Particle Size Distributions of Colloidal Silica Abrasives Used in Chemical-Mechanical Planarization

Abstract: Particle size distribution (PSD) analysis of colloidal silica abrasives employed in chemical-mechanical planarization slurries is demonstrated using fluorescence correlation spectroscopy (FCS). FCS allows a quantitative determination of the PSD for a dispersion of abrasive silica particles through fluorescence measurements of a dye, Rhodamine 110 (R110), adsorbed to the particles. Analysis of the autocorrelation function (ACF) of the fluorescence intensity fluctuations from R110-dyed silica confirms the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…20 In the present study, the analytical capabilities of one particular single-molecule spectroscopic technique, fluorescence correlation spectroscopy (FCS), 18 are highlighted for colloidal silica dispersions used in CMP processes. This work expands on previously reported preliminary FCS findings for this class of slurries [21][22][23] and identifies future areas of application of the technique for CMP slurry characterization.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…20 In the present study, the analytical capabilities of one particular single-molecule spectroscopic technique, fluorescence correlation spectroscopy (FCS), 18 are highlighted for colloidal silica dispersions used in CMP processes. This work expands on previously reported preliminary FCS findings for this class of slurries [21][22][23] and identifies future areas of application of the technique for CMP slurry characterization.…”
supporting
confidence: 78%
“…Preliminary FCS studies have demonstrated that the copper CMP additives BTA and glycine interact with the surface of a precipitated silica abrasive (d H = 115 ± 1 nm). [21][22][23] As shown in Figure 6, the degree of A546 adsorption was reduced by BTA in silica-dye mixtures. Separate FCS studies confirmed that de-sorption of A546 was not due to a more favorable binding interaction between A546 and BTA in solution.…”
Section: Resultsmentioning
confidence: 80%
“…The characterization of physical properties for colloidal CMP abrasives has been achieved using a host of analytical techniques (3)(4)(5)(6). One method in particular, fluorescence correlation spectroscopy (FCS), has been demonstrated in the analysis of both the surface chemistry and particle diameter distribution of nano-sized silica CMP abrasives (7)(8)(9). In the present study, the capabilities of the FCS technique in the analysis of the physical properties of colloidal ceria CMP abrasives are described.…”
Section: Introductionmentioning
confidence: 99%